A retrospective chart review of opioid-induced nausea and somnolence on commencement for cancer pain treatment - Okamoto, BP, Yoshiaki; Tsuneto, MD, PhD, Satoru; Tsugane, PhD, Mamiko; Takagi, PhD, Tatsuya; Uejima, PhD, Etsuko (Journal of Opioid Management, 2018)
Morphine, oxycodone, and fentanyl are major opioids available as controlledrelease morphine (CRM), controlled-release oxycodone (CRO), and transdermal fentanyl (TDF), respectively, in Japan. The authors conducted a retrospective chart review to examine (1) nausea and somnolence on commencement of CRM, CRO, and TDF for cancer pain treatment, (2) the antiemetic effectiveness of prochlorperazine to prevent opioid-induced nausea, and (3) the side effect of prochlorperazine on somnolence in patients with cancer pain. Four hundred thirteen patients with cancer were prescribed with CRM (N = 66), CRO (N = 196), and TDF (N = 151). The incidence of nausea on commencement of the TDF group (6.8 percent) was significantly lower than that of both the CRM group (22.6 percent) and the CRO group (35.4 percent; p < 0.001). There was no significant difference in the incidence of nausea on commencement of all groups combined with prochlorperazine at dosage of 15 mg/d. The incidence of somnolence on commencement of the TDF group (9.0 percent) was significantly lower than that of both the CRM group (31.3 percent) and the CRO group (41.5 percent; p < 0.001). The incidence of somnolence on commencement of the CRO group combined with prochlorperazine was significantly higher than that of the CRO combined without prochlorperazine (p < 0.05). In conclusion, the incidence of nausea and somnolence on commencement of TDF are significantly lower than that of both CRM and CRO for cancer pain treatment. Prochlorperazine at a dosage of 15 mg/d may not be effective in preventing opioid-induced nausea and may cause somnolence in patients with cancer pain.